Evaluation of commercial property market maturity: a case of Lithuania - Cohen, Viktorija; Galinienė, Birutė (International Journal of Strategic Property Management, 2014)
Property market maturity level is one of the influential factors affecting competitiveness of a country in a global arena. Local economies of Central and Eastern Europe may have reacted differently to the economic globalisation process, but property markets in these countries became very much dependent on global trends in terms of market development, evolution and adaption of practices. This article analyzes scientific observations and aspects of property market evolution, suggests a model of property market evolution and adapts the property market maturity concept, applying it in the case of the Lithuanian commercial property market. This article also presents the results of a survey among the commercial property market actors, which mainly suggests the level of property market maturity. The results indicate that although the overall market degree of maturity still needs to be improved, the elements of professional services, the actors’ activity, the investment market environment and the flow of information ranked better maturity, compared to the other elements used in the study. First Publish Online: 20 Jun 2014